2021
DOI: 10.1186/s12992-021-00669-5
|View full text |Cite
|
Sign up to set email alerts
|

Who suffered most after deaths due to COVID-19? Prevalence and correlates of prolonged grief disorder in COVID-19 related bereaved adults

Abstract: Background Deaths by COVID-19 have left behind nearly 12 million recent bereaved individuals worldwide and researchers have raised concerns that the circumstances of COVID-19 related deaths will lead to a rise prevalence of prolonged grief disorder (PGD) cases. However, to date, no studies have examined the prevalence of PGD among people bereaved due to COVID-19. This study aimed to estimate the prevalence of PGD and investigated demographic and loss-related factors associated with prolonged gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 54 publications
(30 reference statements)
7
94
3
3
Order By: Relevance
“…Despite the rich theoretical discussion on the possible rise of grief during and/or after the pandemic, very little empirical evidence was gathered. Prevalence of PGD in the Chinese bereaved due to COVID-19 was as high as 37.8% (Tang & Xiang, 2021). One study that included 49 Dutch individuals bereaved due to COVID-19 showed that this group of bereaved people reported more severe grief than people bereaved due to natural deaths and an equivalent severity of grief with people bereaved due to unnatural deaths (Eisma, Tamminga, Smid, & Boelen, 2021).…”
Section: Mental Health Outcomes Among People Bereaved Due To Covid-19mentioning
confidence: 99%
“…Despite the rich theoretical discussion on the possible rise of grief during and/or after the pandemic, very little empirical evidence was gathered. Prevalence of PGD in the Chinese bereaved due to COVID-19 was as high as 37.8% (Tang & Xiang, 2021). One study that included 49 Dutch individuals bereaved due to COVID-19 showed that this group of bereaved people reported more severe grief than people bereaved due to natural deaths and an equivalent severity of grief with people bereaved due to unnatural deaths (Eisma, Tamminga, Smid, & Boelen, 2021).…”
Section: Mental Health Outcomes Among People Bereaved Due To Covid-19mentioning
confidence: 99%
“…The high levels of mental health problems may hinder the process of grief adaptation. According to a recent study, researchers found that over one-third of COVID-19 related bereaved Chinese individuals suffered from PGD [31]. The high prevalence demonstrated in the study above validates the importance and urgency of the concerns and early interventions for bereaved individuals due to COVID-19.…”
Section: Bereavement and Grief Under Covid-19 Outbreakmentioning
confidence: 60%
“…The first aim of this project is to train and evaluate Chinese grief consultants with reference to the more developed western grief consultant training system, and to fill the huge gap of grief consulting in China. Secondly, previous studies suggest that related factors (such as unexpected death, social isolation, and multiple losses) may hinder the process of adaptation and recovery of bereaved individuals, but the mechanism remains to be elucidated, so it is necessary to design a longitudinal study to investigate the mental health and associated factors of the bereaved in China [31]. Finally, we set out to develop a grief counseling program suitable for Chinese culture to provide support for bereaved people during COVID-19, while verifying the effectiveness of the design, and supplementing grief research.…”
Section: Rationale For the Researchmentioning
confidence: 99%
“…The author reason that PGD symptoms increase when "deaths are unexpected, traditional grief rituals are absent and physical, social support is lacking." Ishikawa (2020) Older adults Commentary Older adults are expected to experience anticipatory (continued) essential distinguishing factor for grief resulting from COVID death and death due to natural causes, Tang and Xiang (2021) have argued that "the subjective traumatic level of stress" is more significant than the unexpectedness of death for the severity of grief responses.There is a concern among mental health professionals that nonrecognition of the dead, their reduction to mere statistics, and the ambiguity surrounding the death are likely to result in disenfranchised and delayed grief responses. Moreover, for individuals in different life stages, from preschool children to the elderly, the process of grieving may vary.…”
Section: Discussionmentioning
confidence: 99%